A PDE10A inhibitor CPL500036 is a novel agent modulating striatal function devoid of most neuroleptic side-effects - Matloka, Mikolaj; Janowska, Sylwia; Pankiewicz, Piotr; Kokhanovska, Sofiya; Kos, Tomasz; Hołuj, Małgorzata; Rutkowska-Wlodarczyk, Izabela; Abramski, Krzysztof; Janicka, Monika; Jakubowski, Piotr; Świątkiewicz, Maciej; Welniak-Kaminska, Marlena; et al. (Frontiers in Pharmacology, 2022)
Backfround: Phosphodiesterase 10A (PDE10A) is expressed almost exclusively in the striatum and its inhibition is suggested to offer potential treatment in disorders associated with basal ganglia. We evaluated the selectivity, cytotoxicity, genotoxicity, pharmacokinetics and potential adverse effects of a novel PDE10A inhibitor, CPL500036, in vivo. Methods: The potency of CPL500036 was demonstrated by microfluidic technology, and selectivity was investigated in a radioligand binding assay against 44 targets. Cardiotoxicity in vitro was evaluated in human ether-a-go-go related gene (hERG)-potassium channel-overexpressing cells by the patch-clamp method and by assessing key parameters in 3D cardiac spheroids. Cytotoxicity was determined in H1299, HepG2 and SH-SY5Y cell lines. The Ames test was used for genotoxicity analyses. During in vivo studies, CPL500036 was administered by oral gavage. CPL500036 exposure were determined by liquid chromatography–tandem mass spectrometry and plasma protein binding was assessed. The bar test was employed to assess catalepsy. Prolactin and glucose levels in rat blood were measured by ELISAs and glucometers, respectively. Cardiovascular safety in vivo was investigated in dogs using a telemetry method. Results: CPL500036 inhibited PDE10A at an IC50 of 1 nM, and interacted only with the muscarinic M2 receptor as a negative allosteric modulator with an IC50 of 9,2 µM. Despite inhibiting hERG tail current at an IC50 of 21 μM, cardiovascular adverse effects were not observed in human cardiac 3D spheroids or in vivo. Cytotoxicity in vitro was observed only at >60 μM and genotoxicity was not recorded during the Ames test. CPL500036 presented good bioavailability and penetration into the brain. CPL500036 elicited catalepsy at 0.6 mg/kg, but hyperprolactinemia or hyperglycemic effects were not observed in doses up to 3 mg/kg. Conclusions: CPL500036 is a potent, selective and orally bioavailable PDE10A inhibitor with a good safety profile distinct from marketed antipsychotics. CPL50006 may be a compelling drug candidate.